Estimating erosion of cretaceous-aged kimberlites in the Republic of South Africa through the examination of upper-crustal xenoliths - Hanson, Emily Kate (Rhodes University, Faculty of Science, Department of Geology, 2007)
he estimation of post-emplacement kimberlite erosion in South Africa through the study of upper-crustal xenoliths is relatively unexplored; however the presence of these xenoliths has been recognized for well over 100 years. Post-emplacement erosion levels of a small number of South African kimberlite pipes have been inferred through the study of the degree of country-rock diagenesis, the depth of sill formation, the depth of the initiation of the diatreme and fission track studies. Through these studies, several estimates were proposed for the Group I Kimberley kimberlites. Although the 1400 m estimate of erosion remains widely accepted today, this estimate relies on the presence of Karoo-like basalt xenoliths in the Group I Kimberley kimberlites, as their presence proves that basalt existed in the Kimberley area when the kimberlites were emplaced. Basaltic xenoliths were described during the early stages of mining in Kimberley, though only one of these descriptions suggests that the 'basaltic' boulders correlate with the Karoo basalts. Because of the discrepancy between these early documentations of upper-crustal xenoliths and because the occurrence of Karoo-like basalt xenoliths in the Group I Kimberley kimberlites is under question, a re-investigation of the erosion levels and the upper crustal xenolith suites in South African, Cretaceous-aged kimberlites, including Melton Wold, Voorspoed, Roberts Victor, West End, Record Stone Quarry, Finsch, Markt, Frank Smith, Pampoenpoort, Uintjiesberg, Koffiefontein / Ebenheuyser, Monastery, Kimberley (Big Hole), Kamfersdam , Jagersfontein, Kaal Vallei, De Beers, Bultfontein, Lushof, Britstown Cluster, Hebron and Lovedale, was conducted. This study presents the analytical results for upper-crustal sandstone and basalt xenoliths collected from dumps, excavation pits and borehole core at the above-mentioned kimberlites, and demonstrates that they correlate with stratigraphic units of the Karoo Supergroup on the basis of mineral and geochemical compositions. These upper-crustal xenoliths are incorporated into kimberlites and down-rafted to levels below their stratigraphic position during kimberlite emplacement, consequently recording the broad stratigraphy into which each kimberlite is emplaced. Therefore, the Cretaceous lateral extent of the Karoo Supergroup is inferred and post-emplacement erosion estimated by reconstructing the stratigraphy based on upper-crustal xenolith suites for each kimberlite and calculating the total thickness of the now-eroded units. The distribution of sandstone xenoliths indicates that during the Cretaceous the lateral extent of the Dwyka, Ecca and Beaufort Groups encompassed all of the examined kimberlites, while the 'Stormberg' Group was constrained to an area outlined by the Voorspoed and Monastery kimberlites. Similarly, basalt xenoliths occur in all of the Group II and transitional (143 "“ 100 Ma) kimberlites but only in the Group I (90 "“ 74 Ma) kimberlites that lie within close proximity to the western outcrop margin of the outcrop area of the Drakensberg Group basalts (Lesotho Remnant), namely Monastery, Jagersfontein and Kaal Vallei. This trend implies an eastward-retreat of the inland erosion front of the Karoo basalts between 140 and 90 Ma and subsequent erosion of the underlying sedimentary units. It also suggests that a thicker succession of Karoo strata was present at the time of Group II and transitional kimberlite emplacement and that there has been more post-emplacement erosion in these kimberlites than the younger Group I kimberlites, except for Monastery, Jagersfontein and Kaal Vallei. Estimates are unique to each kimberlite as they are dependent on both stratigraphic location, elevation and present country rock, and range from approximately 1000 "“ 2500 m for the older kimberlites and less than 700 m to 1400 m for the younger kimberlites. Furthermore, the upper-crustal xenoliths found at the Group I Kimberley kimberlites and the coinciding trend of basalt erosion demonstrate that Karoo basalts were eroded from the Kimberley area by the time the Group I Kimberley kimberlites erupted (~85 Ma). Therefore, basalts are omitted from the Group I Kimberley kimberlites post-emplacement erosion estimate, and the upper Beaufort Group is considered the upper limit of the stratigraphy that was present at the time of the eruption of the Group I Kimberley pipes. Therefore, the erosion estimates decrease from a previous estimate of 1400 m down to 400 to 1100 m, where 850 m is considered a dependable intermediate estimate.
Keywords: Kimberlite -- South Africa; Igneous rocks -- Inclusions -- South Africa; Erosion -- South Africa